A new large-scale dynamic rig to evaluate rain-wind induced vibrations on stay cables: Design and commissioning. Issue 206 (November 2020) - D'Auteuil, Annick; McTavish, Sean; Raeesi, Arash
Abstract: Cable-stayed bridges are exposed to different weather conditions including wind and rain. The wind can excite the cables causing them to vibrate and this effect can be amplified in the presence of rain. There are a limited number of facilities worldwide capable of testing rain-wind induced vibration (RWIV) on large stay cable models. A new RWIV test rig has been developed for use in the National Research Council 9 ​m Wind Tunnel. The RWIV test rig and rain system were commissioned in July–August 2019. The commissioning study demonstrated the ability of the rig to generate large-amplitude wind-induced vibrations on a cable with a length of 5 ​m and a length-to-diameter ratio of 23. Highlights: Stay cables are getting larger and new testing facilities are needed to accommodate them. A new rain-wind test rig has been developed at National Research Council Canada. The new test rig accommodates full-scale cables models with low blockage ratios. The new test rig successfully reproduced Rain-wind induced vibration of a stay cable model.